The Labor Supply Effects of Delayed First Birth - Herr, Jane Leber (American Economic Review, 2015)
In this paper I compare the relationship between first-birth timing and post-birth labor supply for high school and college graduate mothers. Given that pre-birth wages are increasing in fertility delay, the rising opportunity cost of time would suggest that among both groups, later mothers work more. Yet I only find this pattern for high school graduates. For college graduates, I instead find that there is a strong U-shaped pattern between hours worked within motherhood, and the career timing of first birth.